REALISTIC MATHEMATICS EDUCATION USING PAPAN TAKALINTAR MEDIA TO ENHANCE STUDENTS LEARNING OUTCOMES IN FOURTH GRADE OF ELEMENTARY SCHOOL - Hayati, Zikra; oviana, wati; Jannah, Misbahul; Sari, Novi Trina; Ulya, Khairatul; Zulfita, Dara (Jurnal Ilmiah Didaktika, 2025)
This research explores the implementation of the Realistic Mathematics Education (RME) approach assisted by papan takalintar media to enhance mathematics learning outcomes among fourth-grade students at MIN 8 Southwest Aceh. The study was motivated by students' difficulties in performing multiplication calculations, especially with large-digit numbers, and their lack of accuracy in solving problems. The research aimed to analyze teacher activities, student engagement, and student learning outcomes following the application of this approach. Using a Classroom Action Research (PTK) methodology, the study involved 31 students from class IVA. Data collection techniques included observations and tests, with results analyzed using percentage techniques. The findings showed a significant improvement in teacher activity, which increased from 57.64% in cycle I to 94.11% in cycle III. Similarly, student activity rose from 58.82% in cycle I to 91.76% in cycle III. Student learning outcomes also showed a steady increase, from 48.38% in cycle I to 83.87% in cycle III, meeting the criteria for classical completeness. These results suggest that the integration of the RME approach with papan takalintar media is an effective strategy for improving students' mathematical understanding and accuracy in multiplication operations. This study highlights the potential of contextual learning tools in enhancing student engagement and performance in mathematics education.